Manganese catalyzed N-alkylation of anilines with alcohols: ligand enabled selectivity - Landge, Vinod G.; Mondal, Akash; Kumar, Vinit; Nandakumar, Avanashiappn; Balaraman, Ekambaram (Organic and biomolecular chemistry, 2018)
Ligand enabled Earth-abundant manganese catalyzed N-alkylation of amines with alcohols via a hydrogen auto-transfer strategy is reported. The choice of the ligand plays a significant role in the alcohol reactivity (aliphatic or aromatic) toward N-alkylation reactions.